Rheumatoid Arthritis - Nurul Kusuma Wardani; Reni Hendrarati Masduchi (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory disorder that primarily affects small peripheral joints.  The average annual incidence of RA in the United States is 0.5 per 1000 persons per year. Female : male ratio of 3:1. Onset of the disease can occur at age ranging 20–60 years old. The precise cause of RA is unknown.Major theories mention it’s caused by environmental factors, genetic predisposition or immunogenic.Diagnosis of RA include morning stiffness at least one hour before maximal improvement, arthritis of three or more joints, arthritis of the hand joints, symmetric arthritis, rheumatoid nodules, positive serum rheumatoid factor and radiographic changes (hand and wrist). Rheumatoid arthritis is defined by the presence of four or more criteria and criteria 1 through 4 must be present for at least six weeks.A 44 year-old woman with pain and stiffness in her hand on and off since 10 years ago. She had difficulty doing her daily living activities (ADL) such as taking a bath and vocational activities such as cooking and washing clothes. On examination there were range of motion (ROM) limitation of the elbow, wrist and fingers, boutonnière deformity on left middle finger and right little finger. On X-ray examination we found erosion on finger joints.The rehabilitation program given were ROM exercises, gentle stretching exercises, finger splint and ADL modifications. We advised her to take the rheumatoid medication regularly (meloxicam, methylprednisolon and chloroquin), do exercises, wear the splint, and do the joint protection program. The goals of treatment were pain relief, maintenance of joint range of motion and mobility, further deformity prevent with joint motion modification therefore improving the quality of life.